Sports And Youth Development Among Universities In The West African Region - Deemua, G. A. (Advances in Social Sciences Research Journal, 2019)
In all societies of the world, a virile youth is the bedrock on which national integration and development is predicated. The youths are the background and the building blocks of any nation. Man, today is enjoying lot of luxuries providing by the advanced technological development on one hand and facing lot of physical, mental, emotional, and social problems on the other. Collectively, all these factors affect family life, society and nation adversely in the long run. Further, advancement in recreational gadgets like T.V., Cable T.V., Video-CD games, computer games have made the child to have less interest in physical activity training resulting in some many crimes and delinquencies among children and youths. The nexus between youth and sport is development. Absolutely, sport if properly managed can be used to develop and take the youths out of the street and provide opportunities for youths to learn some of life’s importance lessons for a better youthful society. The focus of this paper is to examine sports as a veritable tool for youth development. It highlighted youths skill development in sports, youths sports involvement and crime control, sports and youth restiveness and youth character development. It also presented the challenges facing the youths in sports. It concluded with recommendations which include harnessing the potential of sports by putting in place policies and programmes that can put our youth on the right path at all levels of education.